Cerebral Hemodyanamics in Stable Preterm Infants Before and After Packed Cell Transfusion - Chetan, Chinmay; Zaw, Nyein Nyein; Suryawanshi, Pradeep; Banait, Nishant; Pareek, Prince; Deshpande, Sujata; Gupta, Bhvya; Garegrat, Reema (Journal of Nepal Paediatric Society, 2021)
Introduction: In a year, around 3.5 million preterm deliveries occur in India alone. Some of these babies will require packed cell volume (PCV) transfusion. There is a paucity of robust data on effect of blood transfusions on the cerebral hemodynamic from India. This study was done to see the effect of PCV transfusion on blood flow velocities and resistive index (RI) of anterior cerebral artery (ACA) in stable preterm infants. Methods: A prospective observational study was conducted in a tertiary care hospital in Pune, India. All stable preterm infants (< 37 weeks) receiving PCV transfusion were enrolled. USG Doppler study of ACA was done before and after PCV transfusion. Peak systolic velocity (PSV), end-diastolic velocity (EDV) and RI were measured pre and post PCV transfusion. Results: Thirty infants were included in the study, with median gestation age of 28.8 {interquartile range (IQR), 27-30.55} weeks and median birth weight of 970 {interquartile range (IQR), 869.5 - 1190} grams. There was a significant decrease in PSV pre and post PCV transfusion - 58.46 (± 18.44) cm / sec and 46.34 (± 13.93) cm / sec respectively (p value < 0.001). Changes in RI and EDV were non-significant. Conclusions: PCV transfusion significantly decreased PSV, reflecting improved cerebral oxygenation, and decreased cardiac output after correction of anaemia. Laboratory threshold for PCV transfusion in stable preterm infants are not known. USG Doppler study has the potential to provide one of the objective criteria for PCV transfusion in these infants though large scale randomized controlled trials are needed to prove its efficacy.